2013
DOI: 10.3389/fphar.2013.00158
|View full text |Cite
|
Sign up to set email alerts
|

Mind and body: how the health of the body impacts on neuropsychiatry

Abstract: It has long been established in traditional forms of medicine and in anecdotal knowledge that the health of the body and the mind are inextricably linked. Strong and continually developing evidence now suggests a link between disorders which involve Hypothalamic-Pituitary-Adrenal axis (HPA) dysregulation and the risk of developing psychiatric disease. For instance, adverse or excessive responses to stressful experiences are built into the diagnostic criteria for several psychiatric disorders, including depress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 232 publications
(240 reference statements)
1
27
0
1
Order By: Relevance
“…Clinically relevant depressive symptoms (BDI‐II > 19) could be observed in about 12% of patients in our study cohort and were an independent predictor of increased total costs. Chronic disabling conditions are known to affect psychiatric health in patients . However, data on depression in CIDP patients are still sparse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinically relevant depressive symptoms (BDI‐II > 19) could be observed in about 12% of patients in our study cohort and were an independent predictor of increased total costs. Chronic disabling conditions are known to affect psychiatric health in patients . However, data on depression in CIDP patients are still sparse.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic disabling conditions are known to affect psychiatric health in patients. 20 However, data on depression in CIDP patients are still sparse. A Dutch survey study found a depression frequency of 9% in the immune-mediated neuropathies Guillain-Barré Syndrome and CIDP.…”
Section: Rated Neuromuscularmentioning
confidence: 99%
“…Alternatively, blunted HPAA reactivity may also precede the development of an ED, i.e., represents a pre-morbid condition making individuals more vulnerable to EDs. Therefore, further studies should concentrate on the differences between treated and untreated or in-and outpatients with EDs and consider that changes in HPAA functioning could be dynamic during the course of a psychological disorder [86], warranting longitudinal studies (e.g. [87]).…”
Section: Discussionmentioning
confidence: 99%
“…Although chronic conditions are known to impact adversely on a person's mental state and psychiatric health [24], only a few studies have examined the psychological health status in patients with immune-mediated neuropathies.…”
Section: Anxiety/depression In Immune-mediated Neuropathiesmentioning
confidence: 99%